Improving Goal of Care Discussions in the ICU: A Mixed Method Systematic Review - DiLabio, Nathalie (Université d'Ottawa | University of Ottawa, 2024)
Background: Goals of care (GOC) discussions are crucial for ensuring that patient care aligns with their beliefs, values, and ethics, particularly in the context of the intensive care unit (ICU). While existing literature offers insights into interventions designed to improve GOC discussions, there is a lack of synthesis of these studies, representing a significant gap in the research. Aim: This review aims to identify, describe, and report on the effectiveness of interventions implemented to improve GOC discussions in the adult ICU context. Methods: A mixed-methods systematic review with a narrative summary was conducted. The review was modelled on Joanna Briggs Institute methodology for this review type. Three databases (Medline, Cumulative Index to Nursing & Allied Health, and the Excerpta Medica Database) were searched. The primary outcome extracted and reported on was the effectiveness of the included interventions. Results: 5,558 articles were initially scanned; five studies met criteria for inclusion. Two main categories of interventions were identified: those supporting healthcare professionals (n=4) and those supporting substitute decision makers (n=1). Studies aimed at supporting health care providers effectively improved individual communication skills and confidence, fostered team-based communication skills, and created a supportive environment. The single intervention supporting substitute decision makers was deemed effective by participants and there was a reported increase in the quality of communication between the care team and participants. Conclusion: This review underscores the complex nature of GOC discussions and the need for multifaceted interventions to enhance GOC discussions in ICUs.
Keywords: Goals of Care; Communication; Interventions; Intensive Care Unit; Mixed Method Systematic Review; Effectiveness